2020
DOI: 10.22373/ujhk.v2i2.7657
|View full text |Cite
|
Sign up to set email alerts
|

‘Azl Sebagai Pencegah Kehamilan (Studi Perbandingan Antara Mazhab Hanafi dan Mazhab Syafi’i)

Abstract: ‘Azl mungkin metode kontrasepsi tertua di dunia, karena ‘azl cara efektif untuk mencegah kehamilan.’azl berarti menarik penis dari vagina keluarnya sperma. Pastinya orang yang melakukan ‘azl (senggama terputus) ada maksudnya,seperti menunda kehamilan atau menjaga jarak dari anak sebelumnya. Karena Ketika sperma yang dikeluarkan di luar vagina pasti tidak akan terjadi pembuahan sehingga tidak terjadi kehamilan. Dalam konteks kekinian ‘azl mengalami pergeseran, ini dapat kita lihat dari pelaksanaan maksud dan tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The problem of preventing Pregnancy in this century is an extension of the Azl law. 27 The majority of scholars allow azl based on the hadith of the Prophet Muhammad narrated by a friend of Jabir: 28…”
Section: Trend Childfree Islamic Law Perspectivementioning
confidence: 99%
“…The problem of preventing Pregnancy in this century is an extension of the Azl law. 27 The majority of scholars allow azl based on the hadith of the Prophet Muhammad narrated by a friend of Jabir: 28…”
Section: Trend Childfree Islamic Law Perspectivementioning
confidence: 99%
“…In Indonesia itself, the practice of 'azl is currently carried out by suggesting the use of contraceptives and campaigning for them in the Family Planning (KB) program. 35 Based on the above hadith from Jabir, there is a basis for the permissibility of 'azl. 36 The term i'tizāl in the verse under review is derived from the word 'azl.…”
Section: The Meaning Of I'tizāl In Qs Al-baqarah[2]: 222 Perspective ...mentioning
confidence: 99%
“…with his findings that family planning in Islam is known as 'azl (Al-Fauzi, 2017), then Ade Irwan Gultom, studied family law planning according to Islamic leaders by finding out that there were problems experienced by the family (Gultom, 2020). And Musyid Djawas et al who researched the 'azl law in preventing pregnancy by comparing the Hanafi and Shafi'I schools so that it was found that the Hanafi school allowed 'azl on the basis of the wife's permission, while according to the Shafi'I imam, it was not necessary to ask for permission (Djawas, 2019). Therefore, in this study the authors are interested in studying more deeply and focusing more on examining the comparison of opinions from the two mass organizations in the city of Bandar Lampung regarding family planning law according to LDII and NU figures in the city of Bandar Lampung.…”
Section: Introductionmentioning
confidence: 99%